Thoracoscopic esophagectomy with three-field lymphadenectomy for thoracic esophageal cancer in a patient with a double aortic arch: a report of a case - Hisashi Fujiwara; Takuji Sato; Naoya Okada; Takeo Fujita; Takashi Kojima; Hiroyuki Daiko (Surgical Case Reports)
Abstract Background We encountered an esophageal cancer patient with a double aortic arch (DAA) who underwent radical thoracoscopic esophagectomy with three-field lymph node dissection. A DAA generally makes it difficult to perform upper mediastinal lymph node dissection via both sides of the thoracic cavity. Furthermore, most patients with a DAA have a superior right aortic arch and right-sided descending aorta, which hampers radical esophagectomy with a typical right thoracic approach. We herein report our operative strategy of thoracoscopic esophagectomy via the left side of the thoracic cavity with a preceding cervical procedure. Case presentation A 64-year-old man was diagnosed with esophageal squamous cell carcinoma in the upper esophagus at clinical Stage IIB (cT1bN1M0) according to the UICC-TNM classification 7th edition. First, we planned the preceding cervical procedure to complete upper mediastinal lymph node dissection, as the DAA prevented a bilateral thoracic approach to the upper mediastinum. We then planned the left thoracoscopic procedure to perform lymph node dissection below the left aortic arch, as the patient in our case had a right side-dominant DAA and right-sided descending aorta, as is common in such patients. We identified the bilateral recurrent laryngeal nerves during upper mediastinal lymph node dissection in the preceding cervical procedure and ultimately successfully resected the patient’s esophageal cancer. Conclusion The cervical procedure preceding the left-thoracoscopic approach is reasonable for achieving radical esophagectomy for thoracic esophageal cancer in patients with a DAA.